THE PORTAL «CHILDREN OF UKRAINE» INFORMATION CONTENT - Tetyana V. Kuznetsova; Alla V. Kilchenko; Oksana V. Ovcharuk; Taisiia H. Omelchenko (Інформаційні технології і засоби навчання, 2010)
The paper presents the description of filling of educational portal «Children of Ukraine», shows the samples of forms for preparation of file list and references list, classifier of informational structure and conditions of portal functioning.